Preparation method of light high-strength composite insulator with high electrical insulation performance
By adding CaCO3, MnCO3 and Cr2O3 to the ceramic insulators, and using surface heat treatment and secondary mud coating technology, the problems of frozen cracking and aging of ceramic insulators in extremely cold environments are solved, and the effect of improving frost resistance and interface breakdown is achieved, extending service life and reducing maintenance costs.
Patent Information
- Application Number
- CN202411694279.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
Existing ceramic insulators have problems such as frozen crack aging, reduced strength, and interface breakdown in extremely cold environments, resulting in low reliability, short service life and high maintenance costs.
By adding CaCO3, MnCO3 and Cr2O3 to the ceramic raw materials, and using surface heat treatment and secondary sludge coating technology, an insulator ceramic core rod with gradually increasing density from the inside to the outside is prepared to form a porous structure to improve frost resistance and interface breakdown.
It improves the freezing resistance and interface breakdown of ceramic insulators, reduces density and cost, extends service life, reduces maintenance costs, and ensures the normal operation of the power grid.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a composite insulator. Background Art
[0002] With the rapid development of the national power industry, the scale of the power grid continues to expand, gradually extending to extreme climate areas such as high altitudes and extremely cold weather. The safe and stable operation of the power system is of vital importance. As an important component of the transmission line, the performance of insulator materials directly affects the safe and stable operation of the power system. Insulator materials used in extremely cold areas must have high strength and excellent freeze-thaw resistance.
[0003] Although a lot of research has been done in this field on power safety and stability, and certain achievements have been made, many problems have not been completely solved, and there are still various power safety accidents, especially large-scale power outages caused by natural freezing disasters. For outdoor power transmission lines, their safe and stable operation is directly related to the climate environment in which they are located. Outdoor power grids have suffered freezing disasters many times, resulting in various losses such as ice-covered and broken transmission wires, frozen and cracked insulation controls, and paralysis of power equipment, which have brought harm to society and people's lives.
[0004] At present, the insulators used in transmission lines are made of three materials: ceramic, glass and composite. Ceramic insulators are the most widely used in the insulator industry due to their high mechanical strength, stable chemical properties, good insulation performance and good corrosion resistance. They are increasingly used in the railway traction network power system. However, ceramic insulators are brittle and dense. When operating in extremely cold environments, they may suffer from frost cracking, aging, reduced strength, and interface breakdown. Therefore, they have low reliability, greatly shortening the service life of ceramic insulators. At the same time, they will increase the maintenance cost of insulators, affect the normal operation of the railway power grid, and reduce economic benefits. Summary of the invention
[0005] In order to solve the problems of high density and poor frost resistance of existing ceramic insulators, the present invention provides a method for preparing a lightweight and high-strength composite insulator with high electrical insulation performance.
[0006] The preparation method of the light-weight high-strength composite insulator with high electrical insulation performance of the present invention is carried out according to the following steps:
[0007] 1. Weigh and mix the ceramic raw materials, then wet-mill them in a ball mill to obtain slurry, and then age and knead the slurry to obtain mud;
[0008] The ceramic raw materials are as follows by weight: alumina: 19-30 parts, calcined bauxite: 1-4 parts, feldspar: 26-36 parts, clay: 20-30 parts, calcined kaolin: 20-25 parts, MnCO3: 2-5 parts, Cr2O3: 6-9 parts, CaCO3: 0.2-0.8 parts, water: 50-80 parts;
[0009] 2. Prepare the clay into blanks according to the design and dry them;
[0010] 3. subjecting the obtained dried blank to surface heat treatment; the surface heat treatment process is: placing the blank in a heating furnace at 900-1070°C and heating it for 3-5 minutes;
[0011] 4. Coat the surface of the blank obtained in step 3 with 3-5 mm of secondary mud and dry it;
[0012] The secondary mud material is prepared by weighing and mixing the secondary mud material raw materials, and then wet-milling the raw materials in a ball mill to obtain slurry, and aging and kneading the slurry to obtain the secondary mud material;
[0013] The secondary mud raw materials include, by weight: alumina: 19-30 parts, calcined bauxite: 1-4 parts, feldspar: 26-36 parts, clay: 20-30 parts, calcined kaolin: 20-25 parts, Cr2O3: 6-9 parts, water: 50-80 parts;
[0014] 5. coating the surface obtained in step 4 with glaze to obtain a semi-finished product;
[0015] The glaze comprises, by weight: 22-30 parts of quartz, 12-16 parts of illite, 4-6 parts of white corundum powder, 2-3 parts of nano silicon dioxide, 1-2 parts of wollastonite, 8-9 parts of barium carbonate, 8-10 parts of yew clay, 5-6 parts of aluminum oxide, 1-2 parts of iron oxide, 1-2 parts of copper oxide, 4-5 parts of zirconium oxide, 4-7 parts of sepiolite, 4-7 parts of bentonite, and 60-75 parts of water;
[0016] 6. placing the semi-finished product in a sintering furnace for sintering to obtain an insulator ceramic core rod;
[0017] The sintering process is as follows: the atmosphere is air atmosphere, the heating rate is 4-6°C / min, the temperature is 1050-1180°C, sintering is performed for 1.5-3h, and the furnace is cooled to room temperature;
[0018] 7. Connect the insulator ceramic core rod with the insulator hardware, and form the silicone rubber jacket and shed skirt, and the process is complete. The principles and beneficial effects of the present invention are:
[0019] The present invention adds CaCO3, MnCO3 and Cr2O to the ceramic raw materials. 3,The addition amount of CaCO3 is extremely low, and micropores can be formed inside the matrix after the embryo is calcined, which improves the frost resistance and insulation, and reduces the density of the ceramic insulator. After CaCO3, MnCO3 and Cr2O3 are added, the sintering temperature of the ceramic is reduced by 200°C; after MnCO3 and Cr2O3 are added, the strength of the insulator ceramic core rod is increased by 27%, saving costs. The present invention can remove most of the volatile components in the blank after surface heat treatment of the dried blank, obtain a surface layer with a density greater than that of the inner layer, and then after coating the secondary mud, the secondary mud does not contain CaCO3 and MnCO3, and a more compact surface layer can be obtained. Therefore, the prepared insulator ceramic core rod has a density that gradually increases from the inside to the outside, the center is a porous structure, and the surface layer is a dense structure, which reduces the density of the insulator, thereby reducing the load of the power supply bracket, and the porous structure increases the capacitance of the composite insulator, reduces the generation of corona, and is also conducive to improving the frost resistance and interface breakdown of the ceramic insulator, increasing the service life of the insulator, reducing the maintenance cost, and ensuring the normal operation of the power grid. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0021] Specific implementation method 1: The preparation method of the high electrical insulation performance lightweight high-strength composite insulator of this implementation method is carried out according to the following steps:
[0022] 1. Weigh and mix the ceramic raw materials, then wet-mill them in a ball mill to obtain slurry, and then age and knead the slurry to obtain mud;
[0023] The ceramic raw materials are as follows by weight: alumina: 19-30 parts, calcined bauxite: 1-4 parts, feldspar: 26-36 parts, clay: 20-30 parts, calcined kaolin: 20-25 parts, MnCO3: 2-5 parts, Cr2O3: 6-9 parts, CaCO3: 0.2-0.8 parts, water: 50-80 parts;
[0024] 2. Prepare the clay into blanks according to the design and dry them;
[0025] 3. subjecting the obtained dried blank to surface heat treatment; the surface heat treatment process is: placing the blank in a heating furnace at 900-1070°C and heating it for 3-5 minutes;
[0026] 4. Coat the surface of the blank obtained in step 3 with 3-5 mm of secondary mud and dry it;
[0027] The secondary mud material is prepared by weighing and mixing the secondary mud material raw materials, and then wet-milling the raw materials in a ball mill to obtain slurry, and aging and kneading the slurry to obtain the secondary mud material;
[0028] The secondary mud raw materials include, by weight: alumina: 19-30 parts, calcined bauxite: 1-4 parts, feldspar: 26-36 parts, clay: 20-30 parts, calcined kaolin: 20-25 parts, Cr2O3: 6-9 parts, water: 50-80 parts;
[0029] 5. coating the surface obtained in step 4 with glaze to obtain a semi-finished product;
[0030] The glaze comprises, by weight: 22-30 parts of quartz, 12-16 parts of illite, 4-6 parts of white corundum powder, 2-3 parts of nano silicon dioxide, 1-2 parts of wollastonite, 8-9 parts of barium carbonate, 8-10 parts of yew clay, 5-6 parts of aluminum oxide, 1-2 parts of iron oxide, 1-2 parts of copper oxide, 4-5 parts of zirconium oxide, 4-7 parts of sepiolite, 4-7 parts of bentonite, and 60-75 parts of water;
[0031] 6. placing the semi-finished product in a sintering furnace for sintering to obtain an insulator ceramic core rod;
[0032] The sintering process is as follows: the atmosphere is air atmosphere, the heating rate is 4-6°C / min, the temperature is 1050-1180°C, sintering is performed for 1.5-3h, and the furnace is cooled to room temperature;
[0033] 7. Connect the insulator ceramic core rod and the insulator hardware, and form the silicone rubber jacket and shed skirt to complete the process.
[0034] This embodiment has the following beneficial effects:
[0035] In this embodiment, CaCO3, MnCO3 and Cr2O are added to the ceramic raw material. 3, The addition amount of CaCO3 is extremely low, and micropores can be formed inside the matrix after the embryo is calcined, which improves the frost resistance and insulation, and reduces the density of the ceramic insulator. After the addition of CaCO3, MnCO3 and Cr2O3, the sintering temperature of the ceramic is reduced by 200°C, and the strength of the insulator ceramic core rod is increased by 27% after the addition of MnCO3 and Cr2O3. Cost savings. In this embodiment, most of the volatile components in the blank can be removed after the surface heat treatment of the dried blank, and a surface layer with a density greater than that of the inner layer is obtained. After the secondary mud is coated, the secondary mud does not contain CaCO3 and MnCO3, and a more compact surface layer can be obtained. Therefore, the prepared insulator ceramic core rod has a density that gradually increases from the inside to the outside, the center is a porous structure, and the surface is a dense structure, which reduces the density of the insulator, thereby reducing the load of the power supply bracket, and the porous structure increases the capacitance of the composite insulator, reduces the generation of corona, and is also conducive to improving the frost resistance and interface breakdown of the ceramic insulator, increasing the service life of the insulator, reducing the maintenance cost, and ensuring the normal operation of the power grid.
[0036] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the ball milling process in step 1 is: the ball-to-material mass ratio is 1:0.5, the ball milling time is 3 to 8 hours, and the rotation speed is 100 to 500 r / min.
[0037] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the drying temperature in step two is 25° C. and the drying time is 50 hours.
[0038] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: the ball milling process described in step 4 is: the ball-to-material mass ratio is 1:0.5, the ball milling time is 3 to 8 hours, and the rotation speed is 100 to 500 r / min.
[0039] Specific implementation method five: This implementation method is different from any one of specific implementation methods one to four in that: the drying temperature in step four is 25° C. and the drying time is 4 to 5 hours.
[0040] Specific implementation method 6: This implementation method is different from any one of specific implementation methods 1 to 5 in that: the coating thickness of the glaze in step 5 is 0.1-0.15 mm.
[0041] Example 1
[0042] In order to solve the problems of high density and poor frost resistance of existing ceramic insulators, the present invention provides a method for preparing a lightweight and high-strength composite insulator with high electrical insulation performance.
[0043] 1. Weigh and mix the ceramic raw materials, then wet-mill them in a ball mill to obtain slurry, and then age and knead the slurry to obtain mud;
[0044] The ceramic raw materials are as follows by weight: alumina: 19-30 parts, calcined bauxite: 1-4 parts, feldspar: 26-36 parts, clay: 20-30 parts, calcined kaolin: 20-25 parts, MnCO3: 2-5 parts, Cr2O3: 6-9 parts, CaCO3: 0.2-0.8 parts, water: 50-80 parts; the addition amount of CaCO3 is extremely low, and micropores can be formed inside the matrix after the embryo is calcined, thereby improving the frost resistance and insulation, and reducing the density of the ceramic insulator. After adding CaCO3, MnCO3 and Cr2O3, the sintering temperature of the ceramic is reduced by 200°C, saving costs. After adding MnCO3 and Cr2O3, the flexural strength of the insulator ceramic core rod is increased by 27%.
[0045] The ball milling process is as follows: the ball-to-material mass ratio is 1:0.5, the ball milling time is 3 to 8 hours, and the rotation speed is 100 to 500 r / min;
[0046] 2. Prepare the clay into blanks according to the design and dry them;
[0047] The drying temperature is 25°C and the drying time is 50h;
[0048] 3. subjecting the obtained dried blank to surface heat treatment; the surface heat treatment process is: placing the blank in a heating furnace at 900-1070°C and heating it for 3-5 minutes;
[0049] 4. Coat the surface of the blank obtained in step 3 with 3-5 mm of secondary mud and dry it;
[0050] The secondary mud material is prepared by weighing and mixing the secondary mud material raw materials, and then wet-milling the raw materials in a ball mill to obtain slurry, and aging and kneading the slurry to obtain the secondary mud material;
[0051] The secondary mud raw materials include, by weight: alumina: 19-30 parts, calcined bauxite: 1-4 parts, feldspar: 26-36 parts, clay: 20-30 parts, calcined kaolin: 20-25 parts, Cr2O3: 6-9 parts, water: 50-80 parts;
[0052] The ball milling process is as follows: the ball-to-material mass ratio is 1:0.5, the ball milling time is 3 to 8 hours, and the rotation speed is 100 to 500 r / min;
[0053] The drying temperature is 25°C and the drying time is 4 to 5 hours;
[0054] 5. coating the surface obtained in step 4 with glaze to obtain a semi-finished product;
[0055] The glaze comprises, by weight: 22-30 parts of quartz, 12-16 parts of illite, 4-6 parts of white corundum powder, 2-3 parts of nano silicon dioxide, 1-2 parts of wollastonite, 8-9 parts of barium carbonate, 8-10 parts of yew clay, 5-6 parts of aluminum oxide, 1-2 parts of iron oxide, 1-2 parts of copper oxide, 4-5 parts of zirconium oxide, 4-7 parts of sepiolite, 4-7 parts of bentonite, and 60-75 parts of water;
[0056] The coating thickness of the glaze is 0.1-0.15 mm;
[0057] 6. placing the semi-finished product in a sintering furnace for sintering to obtain an insulator ceramic core rod;
[0058] The sintering process is as follows: the atmosphere is air atmosphere, the heating rate is 4-6°C / min, the temperature is 1050-1180°C, sintering is performed for 1.5-3h, and the furnace is cooled to room temperature;
[0059] 7. Connect the insulator ceramic core rod and the insulator hardware, and form the silicone rubber jacket and shed skirt to complete the process.
[0060] In this embodiment, the surface heat treatment of the dried blank obtained can remove most of the volatile components in the blank, obtaining a surface layer with a density greater than that of the inner part. After coating with secondary mud, the secondary mud does not contain CaCO3 and MnCO3, and a denser surface layer can be obtained. Therefore, the density of the prepared insulator ceramic core rod gradually increases from the inside to the outside, the center is a porous structure, and the surface is a dense structure, which reduces the density of the insulator and thus reduces the load of the power supply bracket. The porous structure increases the capacitance of the composite insulator and reduces the generation of corona. It is also beneficial to improve the frost resistance and interface breakdown of the ceramic insulator, thereby increasing the service life of the insulator, reducing maintenance costs, and ensuring the normal operation of the power grid. The flexural strength of the insulator ceramic core rod prepared in this embodiment reaches 390.59MPa, and the density does not exceed 1.72g / cm 3 The average thermal expansion coefficient (30-800°C) reaches 2.86×10 -6 / ℃, relative dielectric constant (10kHz) reaches 8.3, dielectric loss (10kHz) reaches 4.3×10 -3 , the volume resistivity (25℃) reaches 8.3×10 12 Ω·m.
[0061] Comparative Example 1
[0062] In order to solve the problems of high density and poor frost resistance of existing ceramic insulators, the present invention provides a method for preparing a lightweight and high-strength composite insulator with high electrical insulation performance.
[0063] 1. Weigh and mix the ceramic raw materials, then wet-mill them in a ball mill to obtain slurry, and then age and knead the slurry to obtain mud;
[0064] The ceramic raw materials are as follows by weight: alumina: 19-30 parts, calcined bauxite: 1-4 parts, feldspar: 26-36 parts, clay: 20-30 parts, calcined kaolin: 20-25 parts, water: 50-80 parts;
[0065] The ball milling process is as follows: the ball-to-material mass ratio is 1:0.5, the ball milling time is 3 to 8 hours, and the rotation speed is 100 to 500 r / min;
[0066] 2. Prepare the clay into blanks according to the design and dry them;
[0067] The drying temperature is 25°C and the drying time is 50h;
[0068] 3. coating the surface obtained in step 2 with glaze to obtain a semi-finished product;
[0069] The glaze comprises, by weight: 22-30 parts of quartz, 12-16 parts of illite, 4-6 parts of white corundum powder, 2-3 parts of nano silicon dioxide, 1-2 parts of wollastonite, 8-9 parts of barium carbonate, 8-10 parts of yew clay, 5-6 parts of aluminum oxide, 1-2 parts of iron oxide, 1-2 parts of copper oxide, 4-5 parts of zirconium oxide, 4-7 parts of sepiolite, 4-7 parts of bentonite, and 60-75 parts of water;
[0070] The coating thickness of the glaze is 0.1-0.15 mm;
[0071] Fourth, placing the semi-finished product in a sintering furnace for sintering to obtain an insulator ceramic core rod;
[0072] The sintering process is as follows: the atmosphere is air atmosphere, the heating rate is 4-6°C / min, the temperature is 1251-1379°C, sintering is 1.5-3h, and the furnace is cooled to room temperature;
[0073] 5. Connect the insulator ceramic core rod and the insulator hardware, and form the silicone rubber jacket and shed skirt to complete the process.
[0074] The insulator ceramic core rod prepared in this comparative example has a flexural strength of 307.5 MPa and a density of 2.72 g / cm 3 The average thermal expansion coefficient (30-800°C) is 4.86×10 -6 / ℃, relative dielectric constant (10kHz) is 6.3, dielectric loss (10kHz) is 7.3×10 -3 , volume resistivity (25℃) is 4.2×10 11 Ω·m.
Claims
1. A method for preparing a lightweight and high-strength composite insulator with high electrical insulation performance, characterized in that: The preparation method of a lightweight and high-strength composite insulator with high electrical insulation performance is carried out according to the following steps:
1. Weigh and mix the ceramic raw materials, then wet-mill them in a ball mill to obtain slurry, and then age and knead the slurry to obtain mud; The ceramic raw materials are as follows by weight: alumina: 19-30 parts, calcined bauxite: 1-4 parts, feldspar: 26-36 parts, clay: 20-30 parts, calcined kaolin: 20-25 parts, MnCO3: 2-5 parts, Cr2O3: 6-9 parts, CaCO3: 0.2-0.8 parts, water: 50-80 parts; 2. Prepare the clay into blanks according to the design and dry them; 3. subjecting the obtained dried blank to surface heat treatment; the surface heat treatment process is: placing the blank in a heating furnace at 900-1070°C and heating it for 3-5 minutes; 4. Coat the surface of the blank obtained in step 3 with 3-5 mm of secondary mud and dry it; The secondary mud material is prepared by weighing and mixing the secondary mud material raw materials, and then wet-milling the raw materials in a ball mill to obtain slurry, and aging and kneading the slurry to obtain the secondary mud material; The secondary mud raw materials include, by weight: alumina: 19-30 parts, calcined bauxite: 1-4 parts, feldspar: 26-36 parts, clay: 20-30 parts, calcined kaolin: 20-25 parts, Cr2O3: 6-9 parts, water: 50-80 parts; 5. coating the surface obtained in step 4 with glaze to obtain a semi-finished product; The glaze comprises, by weight: 22-30 parts of quartz, 12-16 parts of illite, 4-6 parts of white corundum powder, 2-3 parts of nano silicon dioxide, 1-2 parts of wollastonite, 8-9 parts of barium carbonate, 8-10 parts of yew clay, 5-6 parts of aluminum oxide, 1-2 parts of iron oxide, 1-2 parts of copper oxide, 4-5 parts of zirconium oxide, 4-7 parts of sepiolite, 4-7 parts of bentonite, and 60-75 parts of water; 6. placing the semi-finished product in a sintering furnace for sintering to obtain an insulator ceramic core rod; The sintering process is as follows: the atmosphere is air atmosphere, the heating rate is 4-6°C / min, the temperature is 1050-1180°C, sintering is performed for 1.5-3h, and the furnace is cooled to room temperature; 7. Connect the insulator ceramic core rod and the insulator hardware, and form the silicone rubber jacket and shed skirt to complete the process.
2. The method for preparing a lightweight and high-strength composite insulator with high electrical insulation performance according to claim 1, characterized in that: The ball milling process in step 1 is as follows: the ball-to-material mass ratio is 1:0.5, the ball milling time is 3 to 8 hours, and the rotation speed is 100 to 500 r / min.
3. The method for preparing a lightweight and high-strength composite insulator with high electrical insulation performance according to claim 1, characterized in that: The drying temperature in step 2 is 25°C and the drying time is 50 hours.
4. The method for preparing a lightweight and high-strength composite insulator with high electrical insulation performance according to claim 1, characterized in that: The ball milling process described in step 4 is as follows: the ball-to-material mass ratio is 1:0.5, the ball milling time is 3 to 8 hours, and the rotation speed is 100 to 500 r / min.
5. The method for preparing a lightweight and high-strength composite insulator with high electrical insulation performance according to claim 1, characterized in that: The drying temperature in step 4 is 25°C and the drying time is 4 to 5 hours.
6. The method for preparing a lightweight and high-strength composite insulator with high electrical insulation performance according to claim 1, characterized in that: The coating thickness of the glaze in step 5 is 0.1-0.15 mm.